1955
DOI: 10.1111/j.1365-2672.1955.tb02065.x
|View full text |Cite
|
Sign up to set email alerts
|

The Disinfectant Properties of Quaternary Ammonium Compounds and Sodium Hypochlorite: A Comparison of Results Using Different Test Methods

Abstract: SUMMARY: On exposing a strain of Bacterium coli 28.D.10 in a surface film at atmospheric temperature to atmospheres of different moisture contents, it was found that for relative humidities between 100 and 66% the numbers of survivors decreased with decreasing humidity. There was also some evidence of a slight increase in survivors for a decrease in relative humidity from 43 to 0%. The percentage of survivors of Bact. coli after exposure to quaternary ammonium disinfectants also decreased with relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1955
1955
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…There are several reasons which make it desirable that tests shall include a comparison of the test material with a standard. Garvie & Clarke (1955), and earlier workers, have shown that any result can be obtained by altering the conditions of the test. The mixed culture inoculum of the can test is subject to slight variation from day to day and this could affect the result seriously if absolute standards were imposed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…There are several reasons which make it desirable that tests shall include a comparison of the test material with a standard. Garvie & Clarke (1955), and earlier workers, have shown that any result can be obtained by altering the conditions of the test. The mixed culture inoculum of the can test is subject to slight variation from day to day and this could affect the result seriously if absolute standards were imposed.…”
Section: Discussionmentioning
confidence: 93%
“…The inhibitor used for QAC solutions is 2% lecithin in 3% Lubrol W. Lubrol is effective in stopping the bactericidal and bacteriostatic action of a QAC with Bact. coli as the test organism, but Garvie & Clarke (1955) have shown that this is not the case with Staph. aureus.…”
Section: (A) the Ean Testmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that bacteria suspended in a disinfectant solution are much more readily killed than when they are deposited on a surface (Garvie & Clarke, 1955), where presumably they are protected in some way. Similarly, organisms on milking equipment treated with normal concentrations of disinfectant survive because'they have not come in contact with it.…”
Section: The Use Of Disinfectant Inhibitorsmentioning
confidence: 99%